2006
DOI: 10.1038/nphys464
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the coherent precession of magnetic domain walls propagating along permalloy nanowires

Abstract: The dynamics of the motion of domain walls (DWs) in magnetic materials has been extensively explored theoretically 1-3 . Depending on the driving force, conventionally magnetic field and, more recently, spin-polarized current 4-13 , the propagation of DWs changes from a simple translation to more complex precessional modes 14 . Experimentally, indirect evidence of this transition is found from a sudden drop in the wall's velocity [15][16][17][18] , but direct observation of the precessional modes is lacking. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
211
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(227 citation statements)
references
References 23 publications
(35 reference statements)
12
211
0
4
Order By: Relevance
“…The DW velocities measured on this sample are to our knowledge the highest observed to this day on any DMS. Moreover, they are close to -if not higher than -typical DW velocities encountered on unpatterned 6 and patterned 24 Permalloy. The observed velocities are moreover much higher than those measured on out-of-plane magnetized GaMnAs samples (field-25 or current-induced 26 propagation) where they could only be measured up to a few tens of m s −1 .…”
mentioning
confidence: 80%
“…The DW velocities measured on this sample are to our knowledge the highest observed to this day on any DMS. Moreover, they are close to -if not higher than -typical DW velocities encountered on unpatterned 6 and patterned 24 Permalloy. The observed velocities are moreover much higher than those measured on out-of-plane magnetized GaMnAs samples (field-25 or current-induced 26 propagation) where they could only be measured up to a few tens of m s −1 .…”
mentioning
confidence: 80%
“…This is due to the fact that the nucleated vortex reverses the direction of the magnetic moments in the domain wall. 5,8 This means that the transverse field oscillates between parallel and antiparallel alignments with the moments in the domain wall, effectively leaving the average motion unchanged.…”
Section: ͑1͒mentioning
confidence: 99%
“…The critical field at which wall velocity is the greatest is called the Walker field, above this field the wall progresses slowly along the wire in a series of periodic steps. [6][7][8] Previous attempts have been made to increase the maximum domain wall speed and the value of the critical field. 5,9 The addition of edge roughness in a nanowire has been shown to increase the critical field by effectively suppressing the processional coherence of the magnetic moments in the wire.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of CIDWM was first investigated. The microscopic structure of a DW was observed by using advanced imaging techniques, [21][22][23] from which it was found that there are four types of DWs: transverse and vortex DWs with clockwise and counterclockwise spin rotation. It was revealed that among the DW types, the vortex DW is more mobile than the transverse one.…”
Section: Progress In Study Of Current-induced Domain Wall Motionmentioning
confidence: 99%